2010
DOI: 10.2174/156720110790396508
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Exposure to Antidepressants and the Risk of Spontaneous Abortion: A Review

Abstract: This review suggests that gestational exposure to antidepressants, especially paroxetine and venlafaxine, can lead to spontaneous abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 58 publications
(72 reference statements)
1
12
0
Order By: Relevance
“…11 However, Broy and Bérard, who also included studies published in 2009, reported an increased risk of spontaneous abortion associated with the overall use of antidepressants, specifically paroxetine and venlafaxine. 12 Most of the above studies had limitations such as insufficient power; inefficient study design; potential misclassification of study outcome or exposure owing to maternal recall; lack of complete information on exposure including type, timing and dosage of antidepressant; and the inability to fully address potential confounders, especially indication for use of antidepressants. 8,11 Nevertheless, our findings are similar to those of Einarson and colleagues, who showed that overall antidepressant use during early gestation increased the risk of spontaneous abortion by 63%.…”
Section: 12mentioning
confidence: 99%
See 1 more Smart Citation
“…11 However, Broy and Bérard, who also included studies published in 2009, reported an increased risk of spontaneous abortion associated with the overall use of antidepressants, specifically paroxetine and venlafaxine. 12 Most of the above studies had limitations such as insufficient power; inefficient study design; potential misclassification of study outcome or exposure owing to maternal recall; lack of complete information on exposure including type, timing and dosage of antidepressant; and the inability to fully address potential confounders, especially indication for use of antidepressants. 8,11 Nevertheless, our findings are similar to those of Einarson and colleagues, who showed that overall antidepressant use during early gestation increased the risk of spontaneous abortion by 63%.…”
Section: 12mentioning
confidence: 99%
“…Two recent reviews of the association between exposure to antidepressants during early pregnancy and the risk of spontaneous abortion reported contradictory findings. 11,12 We investigated the risk of spontaneous abortion associated with different classes, types and doses of anti depressants during pregnancy, adjusting for indication for use.…”
mentioning
confidence: 99%
“…The effects of the drug are of concern as most of the ADs have the ability to cross the placental barrier in varying and unpredictable quantities (Hostetter et al, 2000;Dalmizrak et al, 2012). There are some clinical studies reporting maternal/neonatal toxicity and withdrawal symptoms attributed to maternal VEN exposures (Broy and Berard, 2010;Nakhai-Pour et al, 2010;Oberlander et al, 2004;Laine et al, 2003;De Moor et al, 2003;Einarson et al, 2001), but these reports are sketchy and inconclusive in nature and the safety of in-utero exposure to VEN especially in terms of fetal/neonatal neurotoxic and neurodegenerative potential has not been established so far. There are evidences that several teratogens (drugs and/or environmental factors) affect the embryo-fetal development by increasing its free radical load and oxidative stress by producing excessive reactive oxygen species (ROS) due to bioactivation (Ornoy, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…33 Broy and Bérard demonstrated a significant association between the use of the antidepressants paroxetine and venlafaxine and spontaneous abortions. 34 However, the risk-benefit debate for a fetus exposed to SSRIs is still ongoing and, as such, it is not entirely clear whether or not mothers who use SSRIs during pregnancy for depression/stress may also adversely affect the neurological development of their fetuses. 35 One might consider that the pathology related to the serotonin functional polymorphism is not only related to the central neurological/neurotransmitter effect but rather consider ancillary peripheral functions of serotonin based on its placental and myometrial expression.…”
Section: Discussionmentioning
confidence: 99%